Lower ureteral compression through external vascular elongation in a cyclist: A case report. (June 2021) - Ramesmayer, Christian; Mitterberger, Michael; Oberhammer, Lukas; Kunit, Thomas; Lusuardi, Lukas
Abstract: Introduction and importance: There is sparse literature about lower ureteric obstruction due to aberrant blood vessels. We report a case of a patient who was referred to our hospital due to left sided flank pain caused by external compression of the distal ureter. Case presentation: A 47-year-old male patient presented with left sided flank pain. A computed tomography scan revealed external compression of the lower ureter. Hypertrophy of the psoas muscle due to extensive cycling for 20 years lead to concomitant kinking and elongation of the iliacal vessels which caused the distal ureteric obstruction. Robotic-assisted laparoscopic ureterocystoneostomy with psoas hitch technique was performed. Clinical discussion: Lower ureteric obstruction, mostly seen in children, is mostly caused by vascular anomalies such as a persistent umbilical artery. After literature review, we presume it to be the first reported case of distal ureteric obstruction caused by external vascular elongation. Conclusion: The external elongation of pelvic vessels due to excessive cycling and the concomitant extrinsic compression of the distal ureter should be considered as rare but possible cause of lower uretic obstructions. Highlights: A 47-year-old cyclist was admitted with left sided flank pain Excessive cycling lead to elongation of the iliacal vessels and concomitant hydronephrosis External compression of distal ureter due to pelvic elongation is a rare differential diagnosis of lower ureteric obstruction Robotic assisted ureterocystoneostomy as a treatment option was performed